Hiroshima Mon Amour e a recepção da crítica no Brasil - Gomes, Regina (Imagofagia, 2021)
Sobre Brum, Alessandra. Hiroshima Mon Amour e a recepção da crítica no Brasil. São Paulo: Annablume, 2014, 244pp., ISBN: 978-85-391-0641-7.